The use of artificial intelligence Tools in scientific research in the field of social and human sciences advantages and limits - Zaabta, Sirine Hadjar; Sebbagh, Omar (Journal of Human Sciences, 2023)
The study aims at indentfying a set of artificial intellignce tools that benefit the resercher and help him in preparing acientific research in the following aspects : Research and investigation Writing and editing, academic communication, documentation and citation, previous studies, translation, field studies, building measurement tools, data analysis, organizing ideas, time management, defining a plan and defining an appropriate methodology.It is done by spotlight on artificial intelligence and its ethics in scientific research, as well as using its tools in social and human research by defining it, ways to implement it and how to use it, and establishing its link, in order to reach a target in which it benefits the researcher in social and human sciences to benefit from the applications of artificial intelligence.